The Urgency of Digital Literacy and Ethics for Parents in Educating Children in the Digital Age - Karinta Utami; Seni Apriliya; Erwin Saputra (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
The purpose of this study is to examine the level of digital literacy and ethics among parents with primary school-aged children in the digital era. This study  employed a descriptive  method   with a quantitative approach. The participants in this study were 54 parents with children in primary school aged 4–6 in Tasikmalaya City, West Java Province. The research instrument  utilized a questionnaire adapted from government policy on digital ethics, which included four components: digital ethics, understanding of negative content, fundamental knowledge of interaction, participation, and collaboration, and basic knowledge of internet transactions. A descriptive data analysis technique was utilized to investigate the discovered data. The findings revealed that parents' understanding of digital literacy and ethics as a provision for their children's education at home was in the high category. This shows that the government's policies on digital literacy and ethics have been implemented and understood by parents. Furthermore, the functional characteristics include a high infrastructure for accessing the internet at home, demonstrating the ease of accessing the internet or digital media.